Three of a Kind? The Special Case of Australia's Island Councils. Issue 3 (29th May 2015) - Sinnewe, Elisabeth; Kortt, Michael A.; Dollery, Brian; Hayward, Philip
<x xml:space="preserve">Abstract</x> In common with many other countries, Australian local government policy‐makers have focussed heavily on improving financial sustainability and operational efficiency through structural change and other modes of systemic reform. However, this system‐wide approach cannot adequately deal with small island councils due to their sui generis characteristics. In an effort to fill this gap in the literature, this article examines the financial sustainability of Australia's three island councils – Flinders, Kangaroo and King – over the period 2008–2013 in order to determine whether alternative organisational arrangements may be better suited to their unique circumstances. In so doing, our study contributes to the literature by providing the first empirical analysis of the financial viability of Australia's island councils while considering the need for an alternative organisation entity in an effort to enhance their long‐term financial sustainability.